2002
DOI: 10.1300/j012v13n02_04
|View full text |Cite
|
Sign up to set email alerts
|

Girls' Delinquency and the Justice Implications of Intake Workers' Perspectives

Abstract: This research examines the legal processing of girls in the context of intake workers' perceptions of girls' delinquency in a large southwestern county in which Mexican-Americans are the numerical majority. Using official records and in-depth interviews, girls' delinquency and the complexities of intake workers' perceptions of gender, ethnicity and social class are examined. With the exception of a low number of referrals for drugs, girls were referred for those offenses most common among girls nationally: sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…A few officers in this study commented that gender-specific programming is present in detention, but not before that point. We know that detention and other forms of institutionalization are used in place of programs because either there are no services available or there is a lack of spaces in the programs that do exist (Bond-Maupin et al 2002). Gaarder and Belknap's (2002) research on girls sentenced to adult prison found that of the 22 studied, five had no prior record, and 10 had never been placed in foster care, residential treatment, or a long-term correctional program before being sentenced to prison.…”
Section: Discussion Of the Fii~ingsmentioning
confidence: 99%
See 3 more Smart Citations
“…A few officers in this study commented that gender-specific programming is present in detention, but not before that point. We know that detention and other forms of institutionalization are used in place of programs because either there are no services available or there is a lack of spaces in the programs that do exist (Bond-Maupin et al 2002). Gaarder and Belknap's (2002) research on girls sentenced to adult prison found that of the 22 studied, five had no prior record, and 10 had never been placed in foster care, residential treatment, or a long-term correctional program before being sentenced to prison.…”
Section: Discussion Of the Fii~ingsmentioning
confidence: 99%
“…Belknap, Holsinger, and Dunn (1997) attribute the differential treatment of girls to stereotypes held by professionals. Studies have found that youth workers perceive girls as "difficult to work with" given their problems and available treatment options (Baines & Alder, 1996;Belknap et al, 1997;Bond-Maupin, Maupin, & Leisenring, 2002). The perceived difficulty in working with girls may be attributed to the lack of training in identifying girls' needs and the lack of appropriate programs to meet these needs.…”
Section: The Disconnect Between Girls' Lives and Treatment Programsmentioning
confidence: 99%
See 2 more Smart Citations
“…Minority girls have been overrepresented at each stage in the juvenile justice process (Bond-Maupin, Maupin, & Leisenring, 2002;Poe-Yamagata & Jones, 2000;Schaffner, 2006;Snyder & Sickmund, 2006). According to Belknap (2001) and others, because the behavior of Black girls conflicts with dominant societal expectations for girls, they are more likely to get in trouble and to be punished more harshly.…”
Section: Recognizing Within Girl Differencesmentioning
confidence: 99%